Design, testing and finite element analysis of an improved precast prestressed beam-to-column joint. (15th November 2019) - Wang, Haishen; Marino, Edoardo M.; Pan, Peng
Highlights: A dissipative resilient precast prestressed beam-to-column joint is proposed. A design procedure of the beam-to-column joint is formulated. Cyclic response and design procedure are experimentally characterized and validated. Dissipation, self-centring and bearing capacities are studied by ABAQUS analysis. Values of design parameters to exploit the features of the joint are proposed. Abstract: A precast prestressed beam-to-column joint for seismic-resistant RC framed structures is proposed and investigated in this paper. The joint is an improved configuration of the one presented by the authors in a previous study. It consists in precast RC beams assembled together with the column by means of prestressed steel strands. In the contact zone, the concrete of beams and column is protected from crushing by means of steel jackets. The two beams framing into the joint are linked by steel bars that yield during earthquake, thus acting as dissipaters. The novelties of this configuration of the joint are in the anchorage of the longitudinal rebars, in the system adopted to connect concrete beams and steel jackets, in the dissipaters, and in the shape of the steel angles that support the beams during the erection of the structure. Design equations are formulated and incorporated into a procedure consistent with the capacity design philosophy. The performance of the proposed joint and the effectiveness of the design procedure are investigated by a quasi-static test of a 3/5 scale specimen and numerical simulations conducted by a refined finite element model built in ABAQUS environment. The obtained results show and quantify the performance achieved in terms of energy dissipation and self-centring capacity, simplicity of fabrication and repair work, and reliability of bearing capacity. Finally, the parameters that control the design procedure are individuated and calibrated.